2019
DOI: 10.2147/ott.s210014
|View full text |Cite
|
Sign up to set email alerts
|

<p>Aberrantly High Expression Of NOK/STYK1 Is Tightly Associated With The Activation Of The AKT/GSK3β/N-Cadherin Pathway In Non-Small Cell Lung Cancer</p>

Abstract: High metastasis is a leading risk factor for the survival of non-small cell lung cancer (NSCLC) and epithelial-mesenchymal transition (EMT) is a vital step of metastasis. The expression of novel oncogene with kinase domain (NOK) has been observed in some human malignancies, including non-small cell lung cancer (NSCLC); however, the biological function of NOK in NSCLC remains unclear. In the study, we explored the function of NOK in NSCLC, with an aim to elucidate the relevant underlying mechanisms. Patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…CTNNB1 is generally considered as an intermediate regulator molecule of the FGF19-FGFR4 signaling pathway [ 28 , 36 , 37 , 38 ]. In addition, a lot of studies have shown that the downregulation of CTNNB1 was associated with the downregulations of CDH2, ALCAM and ICAM1, which is consistent with our results [ 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The extracellular FGF19-FGFR4 signaling pathway mediates the expression of cell adhesion molecules and regulates specific tumorigenic events, including cancer cell proliferation and metastasis, by activating the expression of downstream intracellular genes [ 35 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…CTNNB1 is generally considered as an intermediate regulator molecule of the FGF19-FGFR4 signaling pathway [ 28 , 36 , 37 , 38 ]. In addition, a lot of studies have shown that the downregulation of CTNNB1 was associated with the downregulations of CDH2, ALCAM and ICAM1, which is consistent with our results [ 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The extracellular FGF19-FGFR4 signaling pathway mediates the expression of cell adhesion molecules and regulates specific tumorigenic events, including cancer cell proliferation and metastasis, by activating the expression of downstream intracellular genes [ 35 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 93%
“…Studies have shown that the FGF19-FGFR4 signaling pathway was an effective antitumor target via mediating a lot of intracellular molecules [ 52 , 53 ]. CTNNB1 as an intermediate molecule between the FGF19-FGF4 signaling pathway and adhesion molecules such as ICAM1, CDH2 and ALCAM [ 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 58 ] was downregulated after EPS364 treatment. Hence, we speculated that EPS364 might target the FGF19-FGF4 signaling pathway to regulate the expression of adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that knockdown of GLUT3 diminished cell proliferation and migration driven by STYK1/NOK, demonstrating that GLUT3 may be crucial to STYK1/NOK-mediated malignant transformation and tumorigenesis. Notably, a considerable number of studies have suggested that STYK1/NOK can activate various proliferation-related signaling pathways or molecules (31)(32)(33). A number of the signaling pathways have been reported to strictly regulate the expression and subcellular distribution of GLUTs, for instance, PI3K/Akt/mTOR, hypoxia-inducible factor-1, c-myc and tumor suppressor protein p53 (19,(34)(35)(36), which provides clues for the further exploration of the upstream molecular mechanism of GLUT3 in STYK1/NOK-overexpressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3 has been shown to regulate cyclin D1 proteolysis and subcellular localization, thereby affecting cell cycle and cell proliferation [ 19 ]. Moreover, GSK-3 can also affect the expression of EMT-related genes, thereby regulating cell migration and invasion [ 20 ]. Therefore, we believe that RNCR3 can promote the proliferation, migration, invasion, growth, and metastasis of HCC cells by activating the Akt/GSK3 β signaling pathway.…”
Section: Discussionmentioning
confidence: 99%